The Investigating the Oppression of Toba Batak Women: Call for Empowerment and Woman Leadership - Megawati None Naibaho (Studia Philosophica et Theologica, 2023)
This research has been developed around the two contrasting views/themes of the Toba Batak women's oppression and call for women's empowerment and leadership. It initially explored the philosophy of the Toba Batak society while identifying the forces of Toba Batak women's suppression. It has examined and critically analyzed the Toba Batak society and its patriarchal culture. It has been discovered that the Toba Batak women are subordinated because of an attitude or disposition dictated and perpetuated by the cultural belief systems, especially the social system of the clan (marga), which places women under the authority of men. Consequently, women are considered mere objects to men, particularly in childbearing, because they must be available to produce male children; otherwise, they suffer exclusion from the clan system, including being a leader. In order to gather data and explore the problem more deeply, this research uses a case study and a qualitative method through a literature study. Rethinking Toba Batak Philosophy and family practices involves rethinking the Toba Batak kinship arrangement and embodying it through substitute liberating, non-discriminating practices. In order to construct space to promote equality between men and women in Toba Batak society, the rethinking and counter-acting of patriarchal Toba Batak philosophy and family practices is essential and fundamental. This way, a cultural analysis will create a more appropriate proposal for addressing women's subjection. A culturalist approach (like promoting newer beliefs through habitual alternative practices) may be similarly called forth to foster women empowerment.